Napping Areas and Nap Pods in Academic Library - fauzan hidayatullah; Zhahirah Indrawati Zainuddin; Kadek Aryana Dwi Putra (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: The library is a place for users to find information, as well as a place to improve the intellectual quality of users. Along with changes in learning styles and obtaining changing user information, libraries are required to follow the development and learning styles of users by providing supporting facilities and infrastructure, one of which is napping areas or nap pods. Purpose: The purpose of this study is to determine the importance of implementing a napping area in the library. Method: This study uses qualitative research with a literature study approach that emphasizes the use of reference sources to obtain data from literature. Findings: The results of the study indicate that the provision of a napping area as a temporary resting place for users needs to be facilitated by libraries in universities considering that developed countries have also implemented these facilities. This is done so that users feel comfortable and refreshed to restart their activities in doing academic tasks and improve quality in the world of education. Conclusion: The importance of implementing a napping area in the library can also provide a unique experience and increase the number of visitors who are decreasing day by day, on the other hand it also increases learning commons as an interesting renewal in the library with the existence of a napping area in the library.